Building construction illustrated / Francis D.K. Ching. - Ching, Francis D. K., 1943- (Wiley, 2025)
A visual guide to building construction principles, updated with the latest materials, methods, and systems, this text offers students and practicing professionals the information needed to understand concepts in residential and commercial construction, architecture, and structural engineering. This edition has been revised throughout to reflect the latest advancements in building design, materials, and systems, including resilient design, diagrids, modular foundation systems, smart facade systems, lighting sources, mass timber materials, and more. It features new illustrations and updated information on sustainability and green building, insulation materials, and fire-rated wall and floor assemblies.